Effect of Kaempferia parviflora extract and its polymethoxyflavonoid components on testosterone production in mouse testis-derived tumour cells. (October 2016) - Horigome, Satoru; Maeda, Misato; Ho, Hsin-Jung; Shirakawa, Hitoshi; Komai, Michio
Highlights: Kaempferia parviflora extract and polymethoxyflavonoids boost testosterone secretion. Polymethoxyflavonoids enhance testosterone production via cyclic AMP. Polymethoxyflavonoids inhibit phosphodiesterase and increase production of cyclic AMP. Abstract: Low testosterone is associated with late-onset hypogonadism, age-related disease, type 2 diabetes, and cardiovascular disease. In this study, we investigated the effects of Kaempferia parviflora extract and two of its components, 5, 7-dimethoxyflavone and 5-hydroxy-3, 7, 3′, 4′-tetramethoxyflavone, on testosterone production in mouse testis-derived tumour cells I-10. K. parviflora fractions containing 5, 7-dimethoxyflavone elicited testosterone production in these cells, as did nobiletin, a polymethoxyflavonoid found in citrus species, but not K. parviflora, which was used as a comparative control. Furthermore, we found that these compounds enhanced testosterone production via cyclic AMP (cAMP)/cAMP response element binding protein signalling. In particular, the compounds inhibited activation of phosphodiesterase and thereby increased production of cAMP. These findings support the possibility that K. parviflora extract, 5, 7-dimethoxyflavone, and nobiletin may mitigate age-related disease and hypogonadism by enhancing testosterone production.